Analysis of Fluoride in Tea Dust and Leaves Available in Nagercoil Market of Kanyakumari District - Umayorubhagan, V.; Amaris, M.; Selvaraj, V.; Sri Renganathan, P. (Asian Journal of Chemistry, 2010)
In the present work some divalent transition metal complexes of biologically active ligands are synthesized and characterized.